Self adjustment dynamic in sojourner college students - Fadhilah Al Zahra Harahap (Universitas Pendidikan Ganesha, 2020)
Studying in a university outside hometown is one of the common way for high school graduates to get access to a better quality of higher education. These new students settle down in new surroundings much different from their respective homes. They adapt to adjust to the new situation. This research aims to understand dynamics of self adjustment of the students during their study in Daerah Istimewa Yogyakarta (Special Province of Yogyakarta). The method used in the research was qualitative phenomenology. The writer found that there were five factors that play roles in the adjustment, which are: (1) support; (2) obstacle; (3) character; (4) intrapersonal; and (5) interpersonal.